2011
DOI: 10.1172/jci45434
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy

Abstract: Food allergies affect up to 6% of young children and 3%-4% of adults. They encompass a range of disorders that may be IgE and/or non-IgE mediated, including anaphylaxis, pollen food syndrome, food-protein-induced enterocolitis syndrome, food-induced proctocolitis, eosinophilic gastroenteropathies, and atopic dermatitis. Many complex host factors and properties of foods are involved in the development of food allergy. With recent advances in the understanding of how these factors interact, the development of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
1
31

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 105 publications
1
119
1
31
Order By: Relevance
“…The relationship between the immune mechanism of hypersensitivity reactions and the clinical manifestation and family history of allergic conditions observed in the present study is similar to that reported in the literature [36][37][38].…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between the immune mechanism of hypersensitivity reactions and the clinical manifestation and family history of allergic conditions observed in the present study is similar to that reported in the literature [36][37][38].…”
Section: Discussionsupporting
confidence: 91%
“…SPT of a panel of common allergens was performed in patients with sufficient intact/noninflamed skin (n = 14) and compared with standard clinical positive and negative controls. Because 3 individuals had (51,52). These responses were observed in Was -/-mice on 3 different genetic backgrounds, independent of colonic inflammation, and occurred similarly in mice that were housed under GF settings when compared with those colonized with an SPF flora.…”
Section: Methodsmentioning
confidence: 82%
“…In children, the most common foods able to trigger an immunological response include, but are not limited to, cow's milk, hen's egg, peanut, soybeans, wheat, fish, and tree nuts. Whereas, in adults, the most common food allergies are due to ingestion of peanuts, tree nuts, fish, and shellfish [99][100][101]. In people, most commonly food allergy started in the first 3 years of life; however, several studies have shown that most allergies that begin early in life (e.g., milk, egg, soy, and wheat) are generally outgrown.…”
Section: Food Allergymentioning
confidence: 99%